Role of bulk and Nanosized SiO2 to overcome salt stress during Fenugreek germination (Trigonella foenum- graceum L.). (3rd July 2018) - Ivani, Reihane; Sanaei Nejad, Seyed Hossein; Ghahraman, Bijan; Astaraei, Ali Reza; Feizi, Hassan
ABSTRACT: The effects of bulk and Nanosized SiO2 on seed germination and seedling growth indices of fenugreek under salinity stress were studied in the College of Agriculture, Ferdowsi University of Mashhad, Iran, in 2013. The experimental treatments included 4 levels of salinity stress (0, 50, 100 and 150 mM), 2 concentrations of bulk (50 and 100 ppm), 2 concentrations of nanosized SiO2 (50 and 100 ppm), and control (without any SiO2 types). Seedling growth attributes significantly improved when bulk and nanosized SiO2 concentrations applied singly or with different levels of salt stress. However, they significantly declined with salt application. The adverse effects of salt on shoot, root and seedling lengths were alleviated by application of 50 ppm nanosized SiO2 treatment. Under salt stress condition, addition of 50 and 100 ppm nanosized SiO2 to fenugreek seeds increased shoot, root and seedling dry weights as compared to bulk SiO2 concentrations and control treatments, though 50 ppm nanosized SiO2 was more effective than 100 ppm nanosized SiO2 application. It was concluded that nanosized SiO2 improves growth attributes of fenugreek and mitigate adverse effects of salt stress.